Hepatoprotective Effect of Lantana camara L. Flower Extracts Against Acetaminophen-Induced Liver Injury in Wistar Rats - Hyelda Stephen; Balaraba Bello; Usman Abdulkadir Almujaddid (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Background and Objective: Acetaminophen (APAP) overdose is a leading cause of acute liver failure worldwide. Lantana camara possesses antioxidant and membrane-stabilizing properties, suggesting potential hepatoprotective activity. This study investigates the hepatoprotective effects of L. camara flower extracts against APAP overdose-induced liver damage in rats. The study was conducted at the National Veterinary Research Institute, Vom, from August 1st, 2022, to November 15th, 2022. Dried L. camara flowers were extracted in methanol. Hepatotoxicity was induced in Wistar rats weighing 125±25g with 750 mg/kg APAP on day 6 and pretreated for 5 days with 100, 300, or 500 mg/kg of methanolic L. camara flower extracts (n=5 per group). The rats were then sacrificed and evaluated for prophylactic effect against alterations in liver enzymes (ALT, AST, ALP), albumin, bilirubin, and total protein. Histopathological examination of the liver was also carried out. The groups treated with L. camara flower extracts exhibited dose-dependent prophylactic activity. The 500 mg/kg extract dose showed maximal efficacy with significant (p<0.05) reduction of AST by 63%, ALT by 105%, and ALP by 80%, and near-normalization of bilirubin and protein levels, compared to APAP control. Histology revealed normal hepatic architecture with only mild hepatomegaly at the 500 mg/kg dose. L. camara flower extract exhibited remarkable protective effects against APAP-induced liver damage, as evidenced by biochemical and histological parameters. The 500 mg/kg dose conferred optimal hepatoprotection, validating its potential as an alternative therapy for APAP toxicity.